2004
DOI: 10.1289/ehp.6398
|View full text |Cite
|
Sign up to set email alerts
|

Toward the effective surveillance of hypospadias.

Abstract: Concern about apparent increases in the prevalence of hypospadias--a congenital male reproductive-tract abnormality--in the 1960s to 1980s and the possible connection to increasing exposures to endocrine-disrupting chemicals have underlined the importance of effective surveillance of hypospadias prevalence in the population. We report here the prevalence of hypospadias from 1980 to 1999 in 20 regions of Europe with EUROCAT (European Surveillance of Congenital Anomalies) population-based congenital anomaly regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 28 publications
(37 reference statements)
3
62
1
2
Order By: Relevance
“…For example, the definition of hypospadias has changed over the years (Dolk et al, 2004) and registered rates for cryptorchidism are difficult to compare due to the complexities related to its assessment. Nevertheless, the results of the sensitivity analyses conducted either by selection of registries including only cases of cryptorchidism diagnosed before 1 year of age, or using data from prospective clinical studies of male newborns confirm the correlations observed in all registries except for a decrease in the statistical power in some instances.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the definition of hypospadias has changed over the years (Dolk et al, 2004) and registered rates for cryptorchidism are difficult to compare due to the complexities related to its assessment. Nevertheless, the results of the sensitivity analyses conducted either by selection of registries including only cases of cryptorchidism diagnosed before 1 year of age, or using data from prospective clinical studies of male newborns confirm the correlations observed in all registries except for a decrease in the statistical power in some instances.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypospadias is approximately 4 to 6 in 1,000 male children (Dolk et al 2004;Paulozzi 1999 ; Paulozzi et al 1997 ) . The external genitalia originate from the genital tubercle (GT) by gathering mesenchymal cells at the border of the cloacal membrane.…”
Section: Introductionmentioning
confidence: 99%
“…This number could potentially increase further with age, as the prepuce could only be retracted in two-thirds of the boys at 3 years. The Danish prevalence, even at birth, was considerably higher than previously reported for Denmark or other countries (67)(68)(69)76), but due to the above-mentioned imprecision of registry data and differences in cohort study designs, no temporal trends could be determined with certainty. Again, the geographic difference in the prevalence of hypospadias between the two Nordic countries was in favor of Finland, and thus in line with data on congenital cryptorchidism, semen quality, and testicular cancer incidence.…”
Section: Prevalence Of Cryptorchidism and Hypospadiasmentioning
confidence: 63%
“…Hypospadias are another relatively common malformation with a reported prevalence of 0.7-1.8 out of 1000 newborn boys (67,68). Some reports suggest that there is a rise in the prevalence of hypospadias in several, but not all, regions (52,54,(69)(70)(71)(72)(73).…”
Section: Prevalence Of Cryptorchidism and Hypospadiasmentioning
confidence: 99%